Telegram from Senator Omer L. Rains to Jane Tolmach - Omer L. Rains:::::: (1976)
This June 10, 1976 telegram from Senator Omer L. Rains congratulates Jane Tolmach on her electoral victory. He extended his "heartiest congratulations," wished her luck in the upcoming election, and encouraged her to continue her hard work.